KURIKULUM DARI ASPEK IMTAK DAN IPTEK: INTEGRASI IMAN, TAKWA, DAN ILMU TEKNOLOGI DALAM PEMBENTUKAN MANUSIA UNGGUL - Riyanti (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
Curriculum plays a crucial role in shaping superior individuals who are capable of responding to the development of science and technology without losing the foundation of faith and piety. This study aims to analyze the integration of IMTAK (faith and piety) and IPTEK (science and technology) within the educational curriculum as a strategy for developing competent and well-characterized human resources. The research employs a library study approach by systematically examining theories of Islamic education and contemporary curriculum concepts. The findings indicate that the integration of IMTAK and IPTEK must be designed both conceptually and operationally in learning objectives, content, methods, and assessment. Spiritual values should serve as the foundation for the development of science and technology rather than merely functioning as complementary elements. An integrated curriculum promotes a balance among spiritual, intellectual, and social intelligence. Therefore, the integration of faith, piety, and science and technology constitutes a strategic effort to form superior individuals who are ethical, productive, and adaptive to societal changes.